Pengaruh Informasi Akuntansi Kegiatan Pengendalian Dan Penilaian Resiko Terhadap Kualitas Laporan Keuangan - Situmorang, Frenky; Nainggolan, Susan G.V.; Pane, Yonson (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this research is to identify and measure the relationship of the variable Accounting Information Activities Control and Risk Assessment to the Quality of Financial Reporting both partially and simultaneously. The research method used is associative studies looking at causal relationships in which independent variables affect dependent variables. The survey looked at 37 respondents, including one official in the financial department of the regional secretariat, one officer in the general section of the local secretary, one official at the secretariat of the DPRD, three officers in the body (1 official representing one body), and eight officials in the service. If partly tested, it can be concluded that the accounting information variable has a significant impact on the quality of financial statements, whereas the impact of the control activity variable on financial report quality has no significant impact, and the risk assessment variable influence on financial statement quality as well.